(untitled) (Actualizaciones en Sida e Infectología, 2023)
Objective: To evaluate the prevalence and appropriateness of ceftriaxone after an educational intervention in an emergency department. Methods: Quasi-experimental study, which included a consecutive sampling of unscheduled consultations of adult patients, during 2 months pre-intervention and post-intervention. The intervention consisted of training physicians to limit its indication only to specific clinical situations (meningitis, pelvic inflammatory disease, and acute abdomen). Retrospective data were used, with additional manual chart review, to validate appropriateness of antibiotic initiation and drug appropriateness. Descriptive and analytical statistics were used. Results: Among 28570 visits, 512 received ceftriaxone (1.79%; 95%CI 1.64-1.95), and only 60.54% were hospitalized. Regarding the before-after comparison, we observed a reduction in the rate of use (from 3.66% to 0.63%; p<0.001), the appropriateness in starting an antimicrobial was maintained (from 84.52% to 86.21%; p=0.778), and the appropriateness of ceftriaxone increased significantly (from 41.78% to 84.00% respectively; p<0.001). Additionally, hospital length of stay was reduced (median 6 to 5 days; p=0.014), with no difference in in-hospital mortality (19.44% vs 17.24%; p=0.691), nor in 30-day mortality (23.41% vs 18.96%; p=0.464). Conclusions: This intervention was effective. These findings represent a fundamental step in programs to optimize the use of hospital antimicrobials, aimed at reducing their overuse and consequent resistance.